Welfare Benefits of Intradermal Vaccination of Piglets - Temple, Déborah (Animals (Basel), 2020)
SIMPLE SUMMARY: Vaccination is reported as a stressful and painful event for animals. Very little is known about the welfare benefits of using needle-free intradermal vaccination in pigs. A commercial trial was conducted in Spain to assess whether intradermal vaccination could improve the welfare of growing pigs. The results demonstrated that the needle-free intradermal injection reduced the behavioural reaction at the time of vaccination. Contrary to intramuscular vaccination, intradermal vaccination did not affect general activity, social behaviour and exploratory behaviour of the piglets after the injection. Blood C-reactive protein and Haptoglobin levels were lower in the intradermal group suggesting a decreased acute phase response and reduced muscular damage compared to intramuscular injection. Thus, the needle-free intradermal method of vaccination of pigs represents a less invasive and less painful alternative to conventional intramuscular injections with needles. ABSTRACT: Vaccination is reported as a stressful and painful event for animals. This study investigated whether needle-free intradermal vaccination improves the welfare of weaned pigs through the reduction of stress and pain biomarkers and improvement of behavioural parameters compared to traditional intramuscular injection with a needle. A total of 339 weaned piglets were allocated to 3 treatment groups: Intradermal Application of Liquids (IDAL) pigs, vaccinated against Porcine Circovirus type 2 (PCV2) by means of intradermal vaccination using a needle-free device Porcilis(®) PCV ID; Intramuscular (IM) pigs vaccinated against PCV2 with Porcilis(®) PCV intramuscularly with a needle; CONTROL pigs were managed identically but did not receive any vaccine injection. At the time of the injection, the reaction of IDAL piglets was similar to control piglets, whereas a greater percentage of piglets vaccinated intramuscularly displayed high-pitch vocalizations (7% CONTROL, 7% IDAL, 32% IM) and retreat attempts (3% CONTROL, 7% IDAL, 39% IM). The day after vaccination, IDAL piglets did not differ from the control piglets for any of the behavioural variables studied through scan samplings. IM piglets showed a lower frequency of social negative interactions (p = 0.001) and rope manipulation (p = 0.04) compared to the CONTROL group. Resting postures did not differ between treatments. At 28 h post-vaccination, IDAL piglets presented lower blood C-reactive protein levels (CONTROL = 20 μg/mL; IDAL = 39 μg/mL; IM = 83 μg/mL, p < 0.0001) and blood Haptoglobin (CONTROL = 1.8 mg/mL; IDAL = 1.9 mg/mL vs. IM = 3.1 mg/mL, p < 0.0001) compared to IM piglets. Salivary chromogranin A and alpha-amylase did not differ between treatment groups when measured 25 min post-vaccination. The method of vaccination did not affect the growth of the piglets or their rectal temperature. These results support that needle-free intradermal vaccination reduces vaccination-related pain in growing pigs.